2021
DOI: 10.1111/gcb.15737
|View full text |Cite
|
Sign up to set email alerts
|

Growth resistance and resilience of mixed silver fir and Norway spruce forests in central Europe: Contrasting responses to mild and severe droughts

Abstract: Extreme droughts are expected to increase in frequency and severity in many regions of the world, threatening multiple ecosystem services provided by forests. Effective strategies to adapt forests to such droughts require comprehensive information on the effects and importance of the factors influencing forest resistance and resilience. We used a unique combination of inventory and dendrochronological data from a long‐term (>30 years) silvicultural experiment in mixed silver fir and Norway spruce mountain fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 150 publications
(187 reference statements)
5
42
0
Order By: Relevance
“…Its comparatively high susceptibility to drought has already been highlighted in several studies across Central Europe, supporting the general assumption that spruce is inferior to predicted climatic changes [109][110][111][112]. This is particularly evident in stronger growth reductions, respectively lower drought resistance, in comparison to other species [19,28] and was confirmed for different elevations [113] and drought levels [114]. In the aftermath of the 2003 drought, our analysis showed that most trees barely recovered or even continued to decline in growth.…”
Section: Relationship Between Climate Growth and Tree Sizesupporting
confidence: 86%
See 2 more Smart Citations
“…Its comparatively high susceptibility to drought has already been highlighted in several studies across Central Europe, supporting the general assumption that spruce is inferior to predicted climatic changes [109][110][111][112]. This is particularly evident in stronger growth reductions, respectively lower drought resistance, in comparison to other species [19,28] and was confirmed for different elevations [113] and drought levels [114]. In the aftermath of the 2003 drought, our analysis showed that most trees barely recovered or even continued to decline in growth.…”
Section: Relationship Between Climate Growth and Tree Sizesupporting
confidence: 86%
“…In addition, Giuggiola et al [42] recommended reducing stand density for isohydric tree species, such as N. spruce, to improve the water balance when trees occur near their ecological limit. Such positive effects of lower stand densities on drought response were observed at both the tree [46,47,114] and the stand level [18,136].…”
Section: Influence Of Past Management Strategies On Growth and Drough...mentioning
confidence: 84%
See 1 more Smart Citation
“…This relatively higher stand density could make these forest stands sensitive to future droughts and warming events [66]. Commercial thinning operations could reduce the competition between trees and could increase resilience to upcoming drought events [5,66,78,81,82].…”
Section: Discussionmentioning
confidence: 99%
“…Climate observations at a global scale indicate an increased frequency and severity of drought events [1], though uncertainties remain concerning the responses of tree species to extreme droughts [2]. Tree growth responses to droughts depend on tree and stand characteristics [3][4][5]. Although several studies have investigated the potential impacts of droughts in drought-prone forests (e.g., [6][7][8]), we still need research focusing on identifying the morphological characteristics of vulnerable individuals across different species to accurately prepare and understand drought responses in forests [9].…”
Section: Introductionmentioning
confidence: 99%